Behind her eyes [compact disc, unabridged] : a novel - Pinborough, Sarah, 1972- (New York Times Bestseller Fiction., 2017)
The secretary of a successful psychiatrist is drawn into the seemingly picture-perfect life of her boss and his wife before discovering a complex web of controlling behaviors and secrets that gradually reveal profound and dangerous flaws in the couple's relationship.